Perancangan Video Promosi Randang Jaguang Makranin - Dimas Wahyu Ardiansyah; M. Sayuti (IAM Indonesia, 2024)
Randang Jaguang Makranin is a culinary business originating from West Sumatra, more precisely in Jorong Tambun Ijuak, Nagari Koto Tangah Simalanggang, Kec. Payakumbuh, Kab. Fifty Cities, West Sumatra. Randang Jaguang Makranin is made from the main ingredient, namely corn mixed with shredded beef. Randang Jaguang Makranin is a new variant of randang and ready-to-eat food. Business owner Randang Jaguang Makranin said that the promotional media carried out by the company so far has not been fully effective, this is due to several types of printed promotional media such as x-banners, and the absence of promotional media that has a wide and attractive reach so that there are still many people who have not get to know this Randang Jaguang Makranin product. In accordance with current technological developments, the power of promotional media in the form of video cannot be denied, because video can offer the most interesting way for promotion. It is hoped that this audio visual concept can be used as a medium to provide visualization and convey the aims and objectives of promoting Randang Jaguang Makranin products through the pre-production, production and post-production stages.